(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Currently, one of the most remarkable areas of polymer materials science in the world is the growing interest in the production of secondary materials by recycling polymer waste. The destruction of plastic waste is one of the most pressing problems of our time. Because during the production of all types of plastic products a certain amount of technological waste is generated. In particular, when processing polyethylene (PE), which belongs to the group of polyolefins, and various types of polymer composite materials (PCM), various technological wastes are generated. To correct this deficiency, various chemical additives are added to its composition.